2001
DOI: 10.1002/1521-396x(200111)188:1<127::aid-pssa127>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Efficiency of GaN-Based LEDs

Abstract: In this work, we investigate the extraction efficiency for UV emitting rectangular 300 Â 300 mm 2 gallium nitride (GaN) based light emitting diodes (LEDs) by simulation with a raytracer tool. It is shown that the extraction efficiency depends strongly on slight variations of the absorption in the GaN layers. Furthermore, the influence of the substrate shape is studied. For standard rectangular sapphire substrate based LEDs the calculated extraction efficiency is 12.4%, whereas for silicon carbide substrate bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…In addition, research efforts have integrated ZnO nanostructures on GaN light-emitting diodes for enhanced emission efficiency. [12][13][14] Both AlInGaP-based LEDs with truncated inverted pyramid (TIP) structures and GaN-based LEDs on SiC substrates 15 for the substrate shaping process can enhance light extraction efficiency. The processes included with selective PEC etching process, 16 the controlled wet chemical etching on the AlInN layer, 17 and the oxidizing process 18,19 on the GaN materials can also affect the optical properties of nitride-based devices.…”
Section: Introductionsupporting
confidence: 69%
“…In addition, research efforts have integrated ZnO nanostructures on GaN light-emitting diodes for enhanced emission efficiency. [12][13][14] Both AlInGaP-based LEDs with truncated inverted pyramid (TIP) structures and GaN-based LEDs on SiC substrates 15 for the substrate shaping process can enhance light extraction efficiency. The processes included with selective PEC etching process, 16 the controlled wet chemical etching on the AlInN layer, 17 and the oxidizing process 18,19 on the GaN materials can also affect the optical properties of nitride-based devices.…”
Section: Introductionsupporting
confidence: 69%
“…[3,4] Further simulation work was carried out by Schad et al, and a sidewall angle of 64 • was optimal for a truncated pyramid GaN-based LED on SiC substrate. [6] For the model, the bottom and top sizes are 200 µm × 200 µm and 300 µm × 300 µm, with a total thickness of 100 µm. By means of simulation, we found that as the chip size increases the enhancement of LEE by chip shaping decreases dramatically.…”
Section: Led Chip Designmentioning
confidence: 99%
“…For GaN-based LED chips on SiC substrate, a significant amount of light emission from the active layer is trapped inside the semiconductor structure because of total internal reflection (TIR). The extraction efficiency could be improved using a shaped SiC substrate, [1,2,6] but improvement is relatively small when the chip size exceeds 1 mm × 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Maximizing the fraction of photons generated within the semiconductor quantum wells that actually escapes out of the device structure is a major challenge for any LED design [4]. Even supposing 100% internal quantum efficiency is achieved, the overall wall plug efficiency of the LED will still be poor if the light extraction efficiency is low.…”
Section: Improving Light Extraction Efficiency From Gan-based Led Strmentioning
confidence: 99%